HEART RATE AND PERCEIVED EXERTION RESPONSES TO PROTOCOL INCREMENTAL SPEED DYNAMOMETRY FOR WHEELCHAIRS - Saulo Fernandes Melo de Oliveira; Filipe de Freitas Lima; Williams Rodrigues; Lúcia Inês Guedes Leite de Oliveira; Afonso Augusto Guimarães Bione; Jorge Luiz Brito-Gomes; Raphael José Perrier-Melo; Manoel da Cunha Costa (Journal of Physical Education)
ABSTRACT To check the cardiac and perceptual responses an incremental protocol on the wheelchair dynamometer, eight volunteers were intentionally selected and evaluated in an experimental session using a compact dynamometer for wheelchairs. A standard wheelchair was used by all participants. After familiarization period, there was a progressive protocol, increasing rate of 5% per minute. Heart rate (HR) and rating of perceived exertion (RPE, 6-20) were measured at the end of every minute. HR on stage 8 was higher compared to the stages 1 and 2. The RPE differed in the first 5 stages. There was a high correlation between FP and FC (r = 0.93; p = 0.0006), and between HR and RPE (r = 0.98; p <0.0001). It was concluded that the equipment has specificity for evaluation of kinetic and kinematic variables of the movement in wheelchairs at the expense of cardiac variables.